GRADUATE STUDY OF ACCOUNTING. - Noble, Howard S. (The Accounting Review, 1935)
The article focuses on the graduate study of Accounting by means of a survey of members of the American Association of Schools of Commerce. Statistical surveys of the extent of such activity in the colleges and universities of the country, and patterns for planning graduate work are suggested time and again. Graduate study of accounting includes all courses in accounting which give graduate credit except the introductory course. Generally speaking, such graduate credit involves four factors, students who are graduates, subjects that are advanced, not elementary, instructors qualified to give graduate work, an institution equipped for advanced or graduate study. In order to be considered graduate study of accounting, it is here assumed that there should be undergraduate preparation in accounting. The range of the percentage of students specializing in accounting indicates the uncertainty that characterizes this graduate work. This would seem to give evidence of the undeveloped character of such graduate study.